Analisis Buku Teks Pelajaran IPS Kelas VII Kurikulum 2013 di SMP Se-Kecamatan Ngargoyoso Kabupaten Karanganyar Jawa Tengah - Agustina, Resa; Purnomo, Arif (Sosiolium: Jurnal Pembelajaran IPS, 2021)
Textbooks are one of the important learning resources, so they can support the achievement of learning objectives. Each subject requires at least one relevant and quality textbook. The purpose of this study was to determine the development of materials and evaluation tools developed in the social studies textbooks used in SMP Sekecamatan Ngargoyoso and teachers responses to the textbooks they used. The type of research used is descriptive research with a qualitative approach. Collecting data using interview methods and study documentation. The results show that the books used in SMP Negeri 1 Ngargoyoso and SMP Negeri 2 Ngargoyoso still use the revised social studies textbooks in 2016, but in terms of material development, they are still relevant to the latest KI dan KD, namely Permendikbud number 37 of 2018. The evaluation tools used in the medium level. And the teacher’s response to the texts they use shows that the textbooks are able to help students ini the social studies learning process in terms of the material, the level of difficulty of the questions, and the material presented is still relevant to the students environment.